Value of Contrast-Enhanced Ultrasound in Partially Cystic Papillary Thyroid Carcinomas - Fang, Fengkai; Gong, Yi; Liao, Liyan; Ye, Fei; Zuo, Zhongkun; Qi, Zhang; Li, Xiaodu; Niu, Chengcheng (Frontiers in Endocrinology, 2021)
Partially cystic papillary thyroid carcinomas (PCPTCs) are rarely reported papillary thyroid carcinomas (PTCs) and are usually misdiagnosed as benign nodules. The object of this study was to provide the various sonographic characteristics of partially cystic thyroid nodules for disfferentiation between malignant and benign nodules, including those for conventional ultrasound (US) and contrast-enhanced ultrasound (CEUS). Twenty-three PCPTCs patients and 37 nodular goiters patients were enrolled in this study. We evaluated the size, cystic percentage, solid echogenicity, calcification, vascularity and CEUS parameters for each nodule. The final diagnosis of all patients was confirmed via surgery. Univariate analysis demonstrated that compared with benign nodular goiters, PCPTCs more frequently presented with calcification, hypo-echogenicity of the solid part, hypo-enhancement, heterogeneous enhancement, centrifugal perfusion, peak intensity index < 1, time to peak index ≥ 1 and area under the curve index <1 on pre-operative US and CEUS. Binary logistic regression analysis demonstrated that heterogeneous enhancement, centrifugal perfusion, and peak intensity index < 1 are independent CEUS characteristics related to malignant PCPTCs and can be used for their differentiation from benign nodular goiters (all p < 0.05). Our study indicated that preoperative CEUS characteristics may serve as a useful tool to distinguish malignant PCPTCs from benign thyroid nodules..